Proposal for a substantive analytical procedure to audit interest income on loans in a solidarity association - Sosa Mora, Eduardo (2020)
Substantive analytical procedures allow auditors to examine efficiently some items of the financial statements without performing detailed documentary examinations, usinginstead calculations based on ratios and percentages representative of the relationships between accounts, or between accounts and other non-financial information.To achieve this purpose is necessary that exist conditions that guarantee the credibility of the data and the effectiveness and suitability of the substantive procedures to be applied, such as the presence of plausible and permanent relationships between the relevant variables and the necessary controls that ensure the reliability of the information on which the calculations of those relationships are based. This paper presents the conceptual framework related to substantive analytical procedures in the audit of financial statements and presents a methodological proposal to examine the interest income on loans in an entity dedicated to the placement of credits among its associates